2004
DOI: 10.1111/j.1471-0528.2004.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean section is protective against stress urinary incontinence: an analysis of women with multiple deliveries

Abstract: All women who had three elective caesarean sections were selected from a database of 40,000 women delivering between 1977 and 1998, and age-matched with women having three vaginal births. They all completed a (validated) urinary and bowel symptom questionnaire. Women who had vaginal births had a significantly higher prevalence of stress incontinence but not other urinary or faecal symptoms compared with those delivered by caesarean section. The prevalence of faecal incontinence was lower than the prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 9 publications
0
9
1
5
Order By: Relevance
“…Their findings seem to suggest that pregnancy plays an important role in the development of SUI and that the mode of delivery is not the sole factor. Moreover, they do not support the observations of Chaliha et al [14] who found that patients who had delivered vaginally three times had a significantly higher rate of SUI than those who had undergone three cesareans before labor (36% vs 3%, respectively; p=0.0001). Pertinently, Groutz et al [15] reported no difference between women who had delivered vaginally and those who had undergone cesarean during labor at about 8.7 cm of dilation (10.3% vs 12%, respectively).…”
Section: Discussioncontrasting
confidence: 55%
“…Their findings seem to suggest that pregnancy plays an important role in the development of SUI and that the mode of delivery is not the sole factor. Moreover, they do not support the observations of Chaliha et al [14] who found that patients who had delivered vaginally three times had a significantly higher rate of SUI than those who had undergone three cesareans before labor (36% vs 3%, respectively; p=0.0001). Pertinently, Groutz et al [15] reported no difference between women who had delivered vaginally and those who had undergone cesarean during labor at about 8.7 cm of dilation (10.3% vs 12%, respectively).…”
Section: Discussioncontrasting
confidence: 55%
“…Most epidemiological studies for risk factors of UI also reveal that increasing BMI is positively related to the prevalence of UI [2,[9][10][11][12][15][16][17]. Nevertheless, there were some studies that showed that the increased risk for incontinence was not due to differences in weight [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal delivery, particularly the initial delivery, has been associated with increased odds of UI [4][5][6][7][8]. Cesarean deliveries, on the other hand, have been reported as protective on the development of UI [9][10][11][12][13][14], with risk of UI being about half the risk associated with vaginal deliveries [3,12,13,[15][16][17]. The relationship between parity and subsequent UI is unclear.…”
Section: Introductionmentioning
confidence: 99%